Response Surface Methodology in determining the Temperature and Drying Time of Lactobacilus Casei Probiotic Granules - Sri Nevi Gantini; Ari Widayanti (Budapest International Research and Critics University, 2022)
Lactobacillus casei is a probiotic bacteria that has an important role in maintaining body health, but its use in liquid preparations is still constrained by shelf life. This study aims to determine the effect of temperature and drying time of wet granulation method on the physical and viability of probiotic granules. This research begins with increasing bacterial biomass and then harvesting the bacteria using centrifuge. Bacteria are encapsulated using 2% alginate and mannitol as fillers. It was dried at a temperature and time variation of 13 test formulas that had been designed by central composite design. The optimal temperature and drying time of probiotic granules obtained from Response Surface Methodology is 45 ° C for 2 hours.